A Novel Variant of Avian Reovirus Is Pathogenic to Vaccinated Chickens - Rui Liu; Dan Luo; Jinhui Gao; Kai Li; Changjun Liu; Xiaole Qi; Hongyu Cui; Yanping Zhang; Suyan Wang; Xiaomei Wang; Yulong Gao; Li Gao (Viruses, 2023)
Avian reovirus (ARV) infections, characterized by severe arthritis, tenosynovitis, pericarditis, and poor weight gain, have become increasingly serious in recent years. The economic impact is significant as it causes growth inhibition and immunosuppression. Some commercial poultry in China have been widely vaccinated with available ARV vaccines; however, infections continue to occur even after vaccination. This study aimed to isolate a novel variant, ARV-SD19/11103, from the joint tissues of infected broiler chickens vaccinated with ARV vaccines in Shandong Province. Genetic evolution analysis of the major protective antigen σC gene in ARVs showed that ARV-SD19/11103 was located in the genotype cluster I but not in the same sub-cluster as the S1133 vaccine strain. The amino acid sequence similarity between SD19/11103 and vaccine strains S1133, 1733, and 2408 was <80%. After analyzing the amino acid sequences of the σC protein, 33 amino acid differences were found between the new variant isolate and the vaccine strains. This novel variant showed obvious pathogenicity in specific pathogen-free chicken embryos and chicks and could cause serious disease in chickens vaccinated with commercially available ARV vaccines. Cross-neutralization experiments further demonstrated a significant antigenic difference between the novel variant and genotype cluster I ARV strains. The novel variant strain isolated in this study provides an important theoretical basis for understanding the prevalence and genetic evolutionary characteristics of ARV variant strains in our country. This study identified the causes of ARVs circulating and emphasizes the needs for developing new vaccines against novel ARV variants.